Mitigating the interferences and intruders in cognitive radio networks using an authentication protocol over Reed-Solomon codes. (20th September 2019) - Kumar, C. Pavan; Selvakumar, R.
Cognitive radio networks have emerged as a promising solution for spectrum scarcity problem. Secondary users (unlicensed users) accessing cognitive radio network suffer from continuous unintentional interference from primary users (licensed users). Also, the adversary present in the channel tries to thwart the secondary users' communication. To address these two problems, an inherent authentication protocol is defined over Reed-Solomon codes. Reed-Solomon codes with authentication protocol are used with M-ary frequency shift keying modulation technique, for transmissions over cognitive radio network. Similarly, the received message is demodulated and decoded to get the original information bits at the receiver. The performance of the proposed scheme is given in terms of bit error rate. The experimental results show that the proposed system performs better in terms of BER reduction. Also, it is shown that the proposed scheme is resistant to replay attack, man-in-the-middle and impersonation kind of attacks.